Accidental diagnosis and conservative management of a case of first-trimester caesarean scar ectopic pregnancy - Abbas, Ahmed M.; Ali, Shymaa S.; Nagy, Mohammed; Nasif, Fady (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Cases of Caesarean Scar Ectopic Pregnancy (CSEP) are becoming increasingly common at tertiary care hospitals because of increase in rate of CS. It may lead to horrible consequences, such as uncontrolled bleeding and uterine rupture (UR), which might require hysterectomy and result in subsequent loss of fertility. This report covers a case of a CSEP discovered early at 9 weeks of gestation in a 25-year-old woman coming for antenatal care. Conservative management of the uterus was performed with removal of the sac and repair of the uterine scar. The patient’s postoperative period was uneventful, and she was discharged 3 days after surgery. CSEP should be detected early to prevent its catastrophic sequences. Although it is a rare complication of cesarean section, CSEP must be kept in the minds of obstetricians facing emergency cases.